Rifampicin-isoniazid induced fatal fulminant hepatitis during treatment of latent tuberculosis: A case report and literature review - Khan, Fahmi Yousef (Medknow Publications, 2010)
A 42-year-old Indian man received 450 mg rifampicin (RIF) and 150 mg isoniazid (INH) daily after being diagnosed of a latent tuberculosis infection. Baseline serum aminotransferase and total bilirubin levels were within normal limits. On day 31 of treatment, the patient experienced epigastric discomfort and general malaise and one week later he developed nausea and episodic vomiting. The patient missed his first scheduled clinic appointment and he continued taking RIF-INH despite his symptoms. He visited the tuberculosis clinic on day 47 of treatment where he was found to be jaundiced and his liver enzymes were elevated. RIF-INH was stopped and the patient was admitted to our hospital as a case of RIF-INH induced hepatitis. On the 7th day of hospitalization, the patient developed consciousness disturbance with flapping tremor and high ammonia level. The patient was diagnosed with fulminant hepatic failure and transferred immediately to the medical intensive care unit, where he died 4 days later.